THE EFFECT OF PROBLEM BASED LEARNING MODEL USING MIND MAP ON CRITICAL THINKING ABILITY AND PROBLEM SOLVING SKILL ON HIGH SCHOOL STUDENTS - Novita .; Nurdin Bukit; Makmur Sirait (Universitas Negeri Medan, 2019)
This study aims to analyze the critical thinking skills and problem-solving skills, analyzing whether the improvement of critical thinking skills and problem-solving skills that are taught by the problem-based learning model using mind map better than students who are taught by conventional learning. This research is a quasi-experimental research with two group pretest-posttest design. The research population is all students of class X SMA Negeri 2 Bandar (senior high school) in first semester, academic year 2017/2018. The study sample was taken randomly consisting of 64 students. Class X MIPA-1 is an experimental class, consisting of 32 students with learning problem model learning using mind map. Class X MIPA-3 is a control class consisting of 32 students using conventional learning. The research instrument uses essay test of critical thinking skills and problem-solving skills that have been declared valid. Data analysis using statistical t-test. The results showed that the average value of critical thinking skills and problem-solving skills using conventional learning was 61.09 and 61.88 were in a low category while the students applying the problem-based learning model using mind map were 75.78 and 77.56 are in the moderate category. The result of hypothesis testing using independent sample t-test shows that each significance value (sig) <0.05 is 0.00 then H0 is rejected, it means that the skills of critical thinking and problem-solving skills of students who are treated with problem-based learning model using mind map is better than conventional learning, so it can be concluded that there is the effect of problem based learning model using mind map to improve critical thinking skills and problem-solving skills